Linalool disrupts Escherichia coli biofilms via dual suppression of motility and adhesion - Wang, Lei; Zhang, Jingyan; Xu, Guowei; Guo, Zhiting; Wang, Jiamian; Huang, Liping; Wei, Lei; Wang, Long; Zhang, Kang; Li, Jianxi (Frontiers in Veterinary Science, 2026)
BackgroundBacterial biofilms, characterized by robust antibiotic resistance and involvement in chronic infections, present significant clinical challenges such as endometritis. While linalool as a natural extract exhibits potent antibiofilm properties, its precise mechanisms of action against Escherichia coli (E. coli) remain unclear.MethodsThe inhibitory effect of linalool on E. coli biofilm formation was evaluated using inhibitory curve analysis and scanning electron microscopy. The influence of linalool on flagella and fimbriae formation in E. coli biofilms was assessed through swarming and swimming motility assays, scanning electron microscopy, and qRT-PCR. Viable count assays and confocal laser scanning microscopy were employed to examine the suppression of E. coli adhesion to bovine endometrial epithelial cells by linalool. Furthermore, an in vivo rat intrauterine infection model with E. coli biofilms was established to investigate the anti-adhesion activity of linalool.ResultsIn vitro assays demonstrated concentration-dependent biofilm inhibition by linalool, achieving 99% inhibition at 4 µL/mL, with structural disintegration confirmed through scanning electron microscopy. Mechanistically, linalool disrupted flagellar gene regulation, downregulating fliA and motA while upregulating fliG and fliM, and impaired both swarming and swimming motility. Simultaneously, it suppressed fimbriae-associated genes (csgA, csgD, and fimH), leading to 99% reduction in bacterial adhesion to bovine endometrial epithelial cells and the eradication of 95% of intrauterine biofilms in vivo.DiscussionAs a low-toxicity phytochemical, linalool exhibits a dual-action mechanism in inhibiting E. coli D5 biofilm formation by suppressing motility and blocking adhesion, representing a potent multitarget agent against biofilm-associated infections. Future studies should validate its pharmacodynamics and potential synergies with conventional antibiotics to facilitate clinical application.